Nineteenth workshop on geothermal reservoir engineering: Proceedings - Ramey, H.J. Jr.; Horne, R.J.; Kruger, P.; Miller, F.G.; Brigham, W.E.; Cook, J.W. (Stanford University, 1994)
PREFACE The Nineteenth Workshop on Geothermal Reservoir Engineering was held at Stanford University on January 18-20, 1994. This workshop opened on a sad note because of the death of Prof. Henry J. Ramey, Jr. on November 19, 1993. Hank had been fighting leukemia for a long time and finally lost the battle. Many of the workshop participants were present for the celebration of his life on January 21 at Stanford's Memorial Church. Hank was one of the founders of the Stanford Geothermal Program and the Geothermal Reservoir Engineering Workshop. His energy, kindness, quick wit, and knowledge will long be missed at future workshops. Following the Preface we have included a copy of the Memorial Resolution passed by the Stanford University Senate. There were one hundred and four registered participants. Participants were from ten foreign countries: Costa Rica, England, Iceland, Italy, Japan, Kenya, Mexico, New Zealand, Philippines and Turkey. Workshop papers described the performance of fourteen geothermal fields outside the United States. Roland N. Home opened the meeting and welcomed the visitors to the campus. The key note speaker was J.E. ''Ted'' Mock who gave a presentation about the future of geothermal development. The banquet speaker was Jesus Rivera and he spoke about Energy Sources of Central American Countries. Forty two papers were presented at the Workshop. Technical papers were organized in twelve sessions concerning: sciences, injection, production, modeling, and adsorption. Session chairmen are an important part of the workshop and our thanks go to: John Counsil, Mark Walters, Dave Duchane, David Faulder, Gudmundur Bodvarsson, Jim Lovekin, Joel Renner, and Iraj Ershaghi. The Workshop was organized by the Stanford Geothermal Program faculty, staff, and graduate students. We wish to thank Pat Ota, Ted Sumida, and Terri A. Ramey who also produces the Proceedings Volumes for publication. We owe a great deal of thanks to our students who operate audiovisual equipment and to Xianfa Deng who coordinated the meeting arrangements for the Workshop. Roland N. Home Frank G. Miller Paul Kruger William E. Brigham Jean W. Cook